Review of the online conference "Jehovah's Witnesses and Their Opponents: Russia, the West, and More" - Fylypovyč, Ljudmyla Oleksandrivna (Relihijna svoboda, 2020)
An overview of the online conference "Jehovah's Witnesses and Their Opponents: Russia, the West, and More," held on September 3, 2020 at the initiative of CESNUR